2014
DOI: 10.1155/2014/858293
|View full text |Cite
|
Sign up to set email alerts
|

Functional Stability of Plasminogen Activator Inhibitor-1

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is the main inhibitor of plasminogen activators, such as tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA), and a major regulator of the fibrinolytic system. PAI-1 plays a pivotal role in acute thrombotic events such as deep vein thrombosis (DVT) and myocardial infarction (MI). The biological effects of PAI-1 extend far beyond thrombosis including its critical role in fibrotic disorders, atherosclerosis, renal and pulmonary fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 132 publications
1
39
0
21
Order By: Relevance
“…PAI-1 is known for its role in regulating the balance between the fibrinolytic system and the thrombotic system101147. Previous studies have shown that patients with DM2 have high levels of PAI-1, which acts as an independent thrombotic risk factor1316.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 is known for its role in regulating the balance between the fibrinolytic system and the thrombotic system101147. Previous studies have shown that patients with DM2 have high levels of PAI-1, which acts as an independent thrombotic risk factor1316.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 acts as the main circulating inhibitor of plasminogen activation in the fibrinolytic system1011. In DM2, elevated levels of PAI-1 lead to impaired fibrinolytic function and have been associated with a greater risk of cardiovascular disease1213.…”
mentioning
confidence: 99%
“…Obesity triggers metabolic syndrome, which can lead to atherosclerosis and ischemic heart disease. Increased PAI‐1 levels have been observed in many disease conditions, including obesity . Although visceral fat area was not measured in the present study, blood coagulability was associated with BMI, an indicator of the degree of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Like α2‐AP, PAI‐1 is a member of the serpin family . A variety of cells synthesize PAI‐1, including hepatocytes, adipocytes and endothelial cells . The PAI‐1 gene is located on chromosome 7, and its expression can be induced by several factors such as insulin .…”
Section: Methodsmentioning
confidence: 99%